Coping Strategies of Social Protection Programs for Community Resilience to Climate Shocks in Tana North Sub-County, Tana River County, Kenya - Ikumu, Lucy Wangui; Kathambi, Bessy; Kiemo, Karatu (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
This study examines the effectiveness of coping strategies of social protection programs in enhancing community resilience to climate shocks in Tana North Sub-County, Tana River County, Kenya. Despite its potential as a policy response, the effectiveness of social protection as a coping strategy in fostering community resilience remains underexplored. This study explores coping strategies employed by local communities and analyses the role of social protection interventions in migrating the impacts of climate-related disasters. Using a mix of qualitative and quantitative methods data was collected from 362 respondents, including surveys, interviews, and focus groups.  The research finds that while these programs provide essential immediate relief and improve absorptive capacities, their impact on adaptation and long-term resilience is limited. Challenges such as inadequate coverage, irregular support, and poor integration with broader resilience-building efforts hinder their effectiveness and restrict their ability to foster community resilience to shocks. The study underscores the urgent need to identify best practices and inform policy recommendations for improving adaptation and fostering community resilience to climate shocks in the region.